2013
DOI: 10.3177/jnsv.59.393
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Prevents Adipocyte Hypertrophy and Mitigates Insulin Resistance in Mice with Established Obesity

Abstract: Summary Our group recently demonstrated that simultaneous administration of trehalose with a high-fat diet (HFD) suppresses adipocyte hypertrophy and mitigates insulin resistance in mice. For the present study, we hypothesized that similar effects of trehalose would be observed in mice with previously-established obesity. Obese mice were fed a HFD and drinking water containing 0.3 or 2.5% (weight/volume) trehalose or distilled water (DW) ad libitum for 8 wk. After 7 wk intake of a HFD and trehalose, fasting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Using a metabolic syndrome mouse model, we have previously shown that trehalose intake mitigates insulin resistance and decreases impaired glucose tolerance as assessed using OGTT, and these effects are attributed to the suppression of adipocyte hypertrophy (2,3). In this study, to assess the preventive effect of trehalose on the development of metabolic syndrome, we examined whether this disaccharide suppresses the progression of insulin resistance in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a metabolic syndrome mouse model, we have previously shown that trehalose intake mitigates insulin resistance and decreases impaired glucose tolerance as assessed using OGTT, and these effects are attributed to the suppression of adipocyte hypertrophy (2,3). In this study, to assess the preventive effect of trehalose on the development of metabolic syndrome, we examined whether this disaccharide suppresses the progression of insulin resistance in humans.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were also evident in an established obese mouse model when 0.3% (weight/volume) trehalose was consumed via its addition to drinking water (3). The effective dose was 0.2 g/kg of body weight/d and translated to 10 g/d in humans weighing 50 kg (3). Thus, these findings suggested that ingestion of 10 g/d trehalose is effective for reducing the risk of onset of metabolic syndrome in humans.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…However, studies using mouse models have found that trehalose suppresses adipocyte hypertrophy and mitigates insulin resistance. This could be a cause for concern, as a resistance of the delivered insulin would undermine the stabilizing properties of the polymer [17]. Another potential stabilizer analysed is polyvinyl caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer (Soluplus®).…”
Section: Introductionmentioning
confidence: 99%